2020
DOI: 10.1016/j.ejmg.2019.103754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ECG variables to predict the outcome of genetic testing in hypertrophic cardiomyopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Robyns et al 40 investigated their Belgian HCM cohort and found unexplained syncope to be a significant positive predictor of a genetic mutation. They also found patients with a positive genetic mutation suffered more frequent syncope then those patients with a negative genotype 40 . The 3 most common genes associated with syncope were MYBPC3, MYH7 and TNNT2, and this study was limited due to the fact some patients were tested with the extended gene panel and some were just tested with these 3 mutations mentioned 40 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Robyns et al 40 investigated their Belgian HCM cohort and found unexplained syncope to be a significant positive predictor of a genetic mutation. They also found patients with a positive genetic mutation suffered more frequent syncope then those patients with a negative genotype 40 . The 3 most common genes associated with syncope were MYBPC3, MYH7 and TNNT2, and this study was limited due to the fact some patients were tested with the extended gene panel and some were just tested with these 3 mutations mentioned 40 .…”
Section: Resultsmentioning
confidence: 99%
“…27,28,31,34 It is well known that a common presentation of HCM is unexplained syncope, which later is found to be due to ventricular arrhythmia or LVOT obstruction. Robyns et al 40 investigated their Belgian HCM cohort and found unexplained syncope to be a significant positive predictor of a genetic mutation. They also found patients with a positive genetic mutation suffered more frequent syncope then those patients with a negative genotype.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Lastly, genetic testing in certain cases may contribute to a better risk stratification for SCD by identifying mutations (ie, MYBPC3) associated with lethal arrhythmias. 60…”
Section: Future Perspectivesmentioning
confidence: 99%